2018
DOI: 10.1159/000486743
|View full text |Cite
|
Sign up to set email alerts
|

Association of Circulating Levels of ADMA with Carotid Intima-Media Thickness in Patients with CKD: a Systematic Review and Meta-Analysis

Abstract: Background/Aims: The incidence of cardiovascular disease in patients with chronic kidney disease (CKD) is significantly higher than that in the general population. Carotid intima-media thickness (CIMT) is considered to be an important predictor of atherosclerosis. Asymmetric dimethylarginine (ADMA) acted as an endogenous nitric oxide synthase inhibitor, which was elevated in patients with CKD, but whether plasma ADMA correlate with the CIMT in CKD patients is still not elucidated. Methods: We searched the PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
(25 reference statements)
0
13
1
1
Order By: Relevance
“…Многие исследователи подтверждают риск фор-мирования фиброза у больных ХСН при наличии ХБП, но до сих не определен маркер нарушения кол-лагенолиза, который бы достоверно отражал сдвиг в сторону коллагенообразования [10,11].…”
Section: таблицаunclassified
“…Многие исследователи подтверждают риск фор-мирования фиброза у больных ХСН при наличии ХБП, но до сих не определен маркер нарушения кол-лагенолиза, который бы достоверно отражал сдвиг в сторону коллагенообразования [10,11].…”
Section: таблицаunclassified
“…Hence, research has been conducted aimed at finding serological markers of increased cardiovascular burden. Adult population studies and pilot pediatric reports suggest that asymmetric dimethylarginine (ADMA) could be one of such biomarkers [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…ADMA is an endogenous inhibitor of nitric oxide synthesis by competitive inhibition of L-arginine uptake by endothelial cells [9,10]. Numerous studies in adult population showed positive relation between ADMA and both intermediate end-points [7,8] as well as cardiovascular morbidity and mortality [11,12]. There are limited data on usefulness of ADMA assessment in children with nephrotic syndrome [13], hypertension [14], juvenile idiopathic arthritis [15], and chronic kidney disease [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, plasma levels of asymmetric dimethylarginine (ADMA), known as an eNOS inhibitor, are also often measured. In general, ADMA competitively inhibits the activity of eNOS and reduces the production of NO in endothelial cells; thus, increased ADMA levels are thought to represent endothelial dysfunction 5) . However, measurement of these biomarkers cannot provide information about the kinetics of circulating endothelial cell-derived NO in real-time.…”
Section: Introductionmentioning
confidence: 99%